Treasure fever! - Griffiths, Andy, 1961- (New York : Scholastic, 2009)
Henry and his friends set out to find buried treasure hidden somewhere in the school; but the word gets out and everyone wants the treasure.
3.8
3-6
3-6.
580
Keywords: Treasure troves -- Juvenile fiction; Schools -- Juvenile fiction; Buried treasure -- Fiction; Schools -- Fiction; Buried treasure -- Fiction; School stories